2007
DOI: 10.1074/jbc.m611255200
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Extensions of Deinococcus radiodurans Dps-1 Mediate DNA Major Groove Interactions as well as Assembly of the Dodecamer

Abstract: Dps (DNA protection during starvation) proteins play an important role in the protection of prokaryotic macromolecules from damage by reactive oxygen species. Previous studies have suggested that the lysine-rich N-terminal tail of Dps proteins participates in DNA binding. In comparison with other Dps proteins, Dps-1 from Deinococcus radiodurans has an extended N terminus comprising 55 amino acids preceding the first helix of the 4-helix bundle monomer. In the crystal structure of Dps-1, the first ϳ30 N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 37 publications
(38 reference statements)
9
63
1
Order By: Relevance
“…S3 in the supplemental material), suggesting assembly of a dodecameric particle like that expected for DPS or DPSL, as opposed to the 24-mer common to ferritin and bacterioferritin. While members of the ferritin superfamily are often found as stable oligomers, their assembly states can also be dependent upon changes in pH, salt concentration, metal ions, and temperature (8,12,14,20,30). However, despite surveying a variety of protein concentrations and buffer conditions, we were unable to identify conditions that give a stable dodecamer on the SEC column.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…S3 in the supplemental material), suggesting assembly of a dodecameric particle like that expected for DPS or DPSL, as opposed to the 24-mer common to ferritin and bacterioferritin. While members of the ferritin superfamily are often found as stable oligomers, their assembly states can also be dependent upon changes in pH, salt concentration, metal ions, and temperature (8,12,14,20,30). However, despite surveying a variety of protein concentrations and buffer conditions, we were unable to identify conditions that give a stable dodecamer on the SEC column.…”
Section: Resultsmentioning
confidence: 90%
“…Assays were performed as described previously (8) moles of subunit) in 0.1 M bis-Tris, pH 6.5, 0.3 M NaCl at 22°C. E. coli DPS was used as a positive control, and bovine serum albumin (BSA) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…HU binds to four-way DNA junctions and may be additionally optimized for DNA recombination events by stabilizing recombination intermediates (208,209). Contrary to HU, one of the D. radiodurans Dps ("DNA protection during starvation") proteins, Dps1 (DR2263), was shown to promote DNA compaction in vitro (54) but not in vivo, as its depletion has no effect on genome condensation and cell viability (459). The D. radiodurans SMC ("structural maintenance of chromosomes") protein (DR1471), which is important for genome stabilization and DNA repair in eukaryotes (100, 365) and bacteria (640), has no role in genome condensation in D. radiodurans either (140a).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
“…Editing of the pairing process by mismatch repair proteins is also expected to forestall recombination between nonhomologous fragments (373,490,510). Finally, tethering the ends of a given DSB to prevent them from dissociating via the cohesin-like RecN protein (518) or via genome condensation-promoting proteins, such as HU (459) and Dps1 (54) …”
Section: Fidelity Of Dna Repair In Irradiated D Radioduransmentioning
confidence: 99%
“…Intensive structural research, especially using with X-ray crystallography, has revealed a highly conserved structural fold of proteins within the Dps protein family isolated from different organisms. 12,16,17,[19][20][21][22][23][24][25] However, most of these studies mainly showed structural features common to other ferritins characterized in bacteria, including the paradigmatic ferritin (FtnA) and the hemecontaining bacterioferritin (Bfr), which are composed of at least 12 subunits folded into four-helix bundles and assembled into spherical protein shells as Dps is. 13,26) E. coli Dps has a very compact and stable structure with protrusion of the highly flexible and lysine-rich N-terminus (Fig.…”
Section: Sep22/dps As a Dna-binding Proteinmentioning
confidence: 99%